2022
DOI: 10.1101/2022.07.13.499473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

KsgA facilitates ribosomal small subunit maturation by proofreading a key structural lesion

Abstract: Ribosome assembly is orchestrated by many assembly factors, including ribosomal RNA methyltransferases whose precise role is poorly understood. Here, we leverage the power of cryo-EM and machine learning to discover that the bacterial methyltransferase KsgA performs a novel "proofreading" function in assembly of the ribosomal small subunit by recognizing and partially disassembling particles that have matured but are not competent for translation. We propose that this activity allows inactive particles an oppo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 77 publications
1
14
0
Order By: Relevance
“…Whereas we have demonstrated the feasibility of our approach to resolve a ribosomal structure in situ with one week of processing, addressing specific biological questions will often require further specialized analyses. For example, to resolve, quantify, and spatially locate distinct functional states, one could leverage the generative capacity of tomoDRGN to reconstruct a large ensemble of heterogeneous structures to be queried on a per-particle basis for the occupancy of known structural elements with MAVEn 47,49 . Alternatively, automated (Kinman et al ., in preparation) or expert-guided inspection of such an ensemble could enable the discovery of novel structural states lost through averaging in the consensus refinement.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas we have demonstrated the feasibility of our approach to resolve a ribosomal structure in situ with one week of processing, addressing specific biological questions will often require further specialized analyses. For example, to resolve, quantify, and spatially locate distinct functional states, one could leverage the generative capacity of tomoDRGN to reconstruct a large ensemble of heterogeneous structures to be queried on a per-particle basis for the occupancy of known structural elements with MAVEn 47,49 . Alternatively, automated (Kinman et al ., in preparation) or expert-guided inspection of such an ensemble could enable the discovery of novel structural states lost through averaging in the consensus refinement.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent cryo-EM structures of E. coli KsgA bound to immature 30S ribosomes from the Ortega and Davis groups, a different mechanism from that in Figure 9A was proposed. It was argued that the N-terminal region of KsgA interacts with helix 24 (h24) of 16S rRNA and that this interaction keeps h24 from occluding the KsgA active site (Sun et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…1B). The current model for KsgA function is that it binds a conformation of the 30S ribosome that is off-pathway for maturation and this binding event promotes remodeling of the 30S to an on-pathway conformation (Connolly et al 2008; Sun et al 2023). Since ribosomes are able to assemble in Δ ksgA cells, methylation is not required for ribosome biogenesis but rather promotes KsgA dissociation from the ribosome once the remodeling event has occurred (Connolly et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The development, theoretical foundations, and limitations of this work have been described previously (Zhong et al, 2019;Zhong et al, 2020). We have applied this approach to a number of publicly-available datasets, and found that cryoDRGN can uncover rare structural states in assembling bacterial ribosomes (Sun et al, 2022) and help visualize continuous conformational changes in spliceosome complexes (Zhong et al, 2020). CryoDRGN has also helped visualize a tilting motion of radial spike proteins important in dynein motors and ciliary motility (Gui et al, 2021).…”
Section: Introductionmentioning
confidence: 86%